2017
DOI: 10.15406/jmen.2017.04.00124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of AmpC β -Lactamase-Producing Pseudomonas aeruginosa Isolates From Feacal Matter of Cow

Abstract: The possible contamination of food and/or food-producing animals with multidrug resistant bacteria including AmpC-producing Pseudomonas aeruginosa is considered a potential source for the wide dissemination of AmpC β-lactamase in the community. This portends public health risks for the populace -owing to the multidrug resistant nature of these organisms. There is paucity of data on the prevalence of AmpCproducing bacteria in Abakaliki, Nigeria -which was why this study was carried out. A total of 40 feacal swa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This high rate of MDR could be as a result of unrestricted use of antibiotics by the population who were mainly traders and depend much on self-medication. Multidrug resistant P. aeruginosa develop resistance by various mechanisms like multidrug resistance efflux pumps, production of β-lactamases, aminoglycoside modifying enzymes, and decrease outer membrane permeability; and these properties of the organism contributes to the virulent nature of P. aeruginosa inclusive of its multidrug resistant nature as was previously reported [15,25,26] . Prompt and accurate detection of MDR bacteria from clinical samples is critical to proper patient care -since these measures will provide sound epidemiological data that will guide antimicrobial therapy during treatment.…”
Section: Discussion________________________mentioning
confidence: 84%
“…This high rate of MDR could be as a result of unrestricted use of antibiotics by the population who were mainly traders and depend much on self-medication. Multidrug resistant P. aeruginosa develop resistance by various mechanisms like multidrug resistance efflux pumps, production of β-lactamases, aminoglycoside modifying enzymes, and decrease outer membrane permeability; and these properties of the organism contributes to the virulent nature of P. aeruginosa inclusive of its multidrug resistant nature as was previously reported [15,25,26] . Prompt and accurate detection of MDR bacteria from clinical samples is critical to proper patient care -since these measures will provide sound epidemiological data that will guide antimicrobial therapy during treatment.…”
Section: Discussion________________________mentioning
confidence: 84%
“…Clinicians also routinely use cephalosporin antibiotics to treat common bacterial infections such as diarrhea, skin infection, sexually transmitted diseases, and others. 25 Therefore, it becomes pertinent to protect the aquatic ecosystem from contamination with sewage, as this may facilitate the dissemination of antimicrobial resistance via horizontal transfer of resistance plasmid. 26…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians also routinely use cephalosporin antibiotics to treat common bacterial infections such as diarrhea, skin infection, sexually transmitted diseases, and oth-ers. 25 Therefore, it becomes pertinent to protect the aquatic ecosystem from contamination with sewage, as this may facilitate the dissemination of antimicrobial resistance via horizontal transfer of resistance plasmid. 26 In general, our findings revealed that P. aeruginosa isolated from Kadangaru demonstrated higher resistance to tested antibiotics when compared to isolates from the Miami area (Table 3).…”
Section: Articlementioning
confidence: 99%
“…but are inhibited by β-lactamase inhibitors such as clavulanic acid 2,4,5 . ESBL-producing bacteria are clinically relevant because they exhibit coresistance to other antibiotics 6,7 . The implication is that treatment options for treating infection caused by ESBL-producing bacteria become limited, leading to long hospitalization, infection persistence, and economic loss 8,9 .…”
mentioning
confidence: 99%